SOCIOLINGUISTIC STUDY OF HATE SPEECH AS FOUND IN COMMENTARIES OFINDONESIAN PRESIDENTIAL CANDIDATES’ INSTAGRAM - Sondang Manik; Rony Arahta Sembirig; Jubil Ezer Sihite; Ardiwan Halawa (University of Kuningan, 2025)
This study investigates the sociolinguistic patterns of hate speech directed at the three Indonesian presidential candidates on Instagram during the 2024 election campaign. Grounded in qualitative–descriptive inquiry, the research analyzes 180 public comments using sociolinguistic discourse analysis, thematic categorization, and interpretive frameworks. Findings show that hate expressions are shaped by political identity, emotional intensity, and ideological positioning. Hate directed at Prabowo Subianto is dominated by revenge (30%) and sadism (26.7%), reflecting emotionally charged hostility tied to his long political history. Anies Baswedan receives predominantly instrumental violence (30%) and revenge (28.3%), indicating strategic attempts to delegitimize his credibility and dissatisfaction with his political maneuvers. For Ganjar Pranowo, instrumental violence (36.7%) and ideology-driven attacks (21.7%) are most prominent, embedding him in narratives of systemic distrust and corruption. Across candidates, hate speech operates as a sociolinguistic mechanism for constructing identity, reinforcing group boundaries, and sustaining political polarization in digital spaces. The study contributes to Indonesian sociolinguistic research by offering a context-specific examination of hate speech on Instagram, highlighting its linguistic forms, discursive strategies, and implications for digital political communication, identity construction, and mitigation efforts.